Perceptions of IT knowledge among SMEs operators in Malaysia - Fauzilah, Salleh; Arikah Raja E, Ali; Nur Haizal, Mat Yaakob@Ariffin; Nalini, Arumugam (2012)
The perception of the importance of IT entrepreneurs plays a vital role in influencing the business performance. Positive perception of the importance of IT knowledge is a necessary approach in achieving and determining the adoption of the business marketing goals. This study was carried out to find out the IT knowledge among small and medium industries (SMIs) in Malaysia. The research has seen the perception of SMEs and their views on IT knowledge. The study involved 285 SME businesses throughout the state which are registered with SMIDEC using a random sampling method. A total of 102 (35.7%) questionnaires were used for this study. This study found that the respondents gave a positive perception of the IT knowledge among the small and medium industries and gave many benefits either directly or indirectly to their business. The findings of this study could be used by academicians to study importance of the IT knowledge among the small and medium industries and provide advisory service to SME entrepreneurs who are enthusiastic about online marketing